Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To determine if the equation [tex]\((7 + y)^2 - y^2 = 9x + 12\)[/tex] is linear and, if so, convert it to standard form [tex]\(ax + by = c\)[/tex], follow the steps outlined below:
1. Simplify the left-hand side:
Expand [tex]\((7 + y)^2\)[/tex]:
[tex]\[ (7 + y)^2 = 49 + 14y + y^2 \][/tex]
Subtract [tex]\(y^2\)[/tex] from the expanded form:
[tex]\[ 49 + 14y + y^2 - y^2 = 49 + 14y \][/tex]
Thus, the equation becomes:
[tex]\[ 49 + 14y = 9x + 12 \][/tex]
2. Rearrange the equation to the form [tex]\(ax + by = c\)[/tex]:
Move the terms to one side to arrange the equation into the standard form. Subtract [tex]\(49\)[/tex] and [tex]\(14y\)[/tex] from both sides:
[tex]\[ 49 + 14y - 49 - 14y = 9x + 12 - 49 - 14y \][/tex]
Simplify the equation:
[tex]\[ 0 = 9x - 14y + 12 - 49 \][/tex]
[tex]\[ 0 = 9x - 14y - 37 \][/tex]
[tex]\[ 9x - 14y = 37 \][/tex]
3. Conclusion:
The given equation is linear because it can be rearranged into the standard form [tex]\(ax + by = c\)[/tex] where [tex]\(a = 9\)[/tex], [tex]\(b = -14\)[/tex], and [tex]\(c = 37\)[/tex].
Thus, the standard form of the given linear equation is:
[tex]\[ 9x - 14y = 37 \][/tex]
1. Simplify the left-hand side:
Expand [tex]\((7 + y)^2\)[/tex]:
[tex]\[ (7 + y)^2 = 49 + 14y + y^2 \][/tex]
Subtract [tex]\(y^2\)[/tex] from the expanded form:
[tex]\[ 49 + 14y + y^2 - y^2 = 49 + 14y \][/tex]
Thus, the equation becomes:
[tex]\[ 49 + 14y = 9x + 12 \][/tex]
2. Rearrange the equation to the form [tex]\(ax + by = c\)[/tex]:
Move the terms to one side to arrange the equation into the standard form. Subtract [tex]\(49\)[/tex] and [tex]\(14y\)[/tex] from both sides:
[tex]\[ 49 + 14y - 49 - 14y = 9x + 12 - 49 - 14y \][/tex]
Simplify the equation:
[tex]\[ 0 = 9x - 14y + 12 - 49 \][/tex]
[tex]\[ 0 = 9x - 14y - 37 \][/tex]
[tex]\[ 9x - 14y = 37 \][/tex]
3. Conclusion:
The given equation is linear because it can be rearranged into the standard form [tex]\(ax + by = c\)[/tex] where [tex]\(a = 9\)[/tex], [tex]\(b = -14\)[/tex], and [tex]\(c = 37\)[/tex].
Thus, the standard form of the given linear equation is:
[tex]\[ 9x - 14y = 37 \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.